Two years of TanDEM-X baseline determination. (1st January 2014) - Wermuth, Martin; König, Rolf; Moon, Yongjin; Walter Antony, John Mohan; Montenbruck, Oliver
The TanDEM-X mission is a German dual satellite formation with the task to acquire a global digital elevation model (DEM) by bistatic interferometric synthetic aperture radar (SAR) data takes. In order to reach the intended DEM accuracy, the two satellites are kept in formation with a distance of less than 500 m and the baseline vector between the two spacecraft needs to be determined with an accuracy of 1 mm. The baseline determination uses observations from the onboard GPS receivers. The baseline vector between the satellites is determined by three independent software packages as there is no independent instrument onboard to verify the GPS results. In studies prior to the mission, comparisons between independent software packages showed biases of a few millimetres. In order to ensure the highest accuracy, a baseline calibration and combination process has been installed. The baseline products are validated by dedicated baseline calibration data takes over test sites, where the DEM is well known. Finally, the different solutions are merged in order to further reduce the errors.